2010
DOI: 10.1177/1082013209353986
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Physical Properties of Poly(vinyl chloride)-based Film Coated with ZnO Nanoparticles

Abstract: Nanoparticles of ZnO and their application in coating systems have attracted a great deal of attention in recent years because of its multifunction property, especially antibacterial activity. In this study, antibacterial and physical properties of poly(vinyl chloride) (PVC) based film coated with ZnO nanoparticles were investigated. It was found that the antibacterial action should be attributed to the killing effect property of ZnO nanoparticles. The ZnO-coated films treated by shaking for 10 h exhibited a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(42 citation statements)
references
References 37 publications
2
38
0
2
Order By: Relevance
“…Zhang et al[48] reported that nano size of ZnO was 573 more effective than micro size of ZnO due to easy penetration 574 through cell wall of microorganisms. Excellent antimicrobial activ-575 ity of ZnO NPs against S. aureus and E. coli and the corresponding 576 mechanism of action had also been demonstrated to Li et al 577[49,50].…”
mentioning
confidence: 87%
“…Zhang et al[48] reported that nano size of ZnO was 573 more effective than micro size of ZnO due to easy penetration 574 through cell wall of microorganisms. Excellent antimicrobial activ-575 ity of ZnO NPs against S. aureus and E. coli and the corresponding 576 mechanism of action had also been demonstrated to Li et al 577[49,50].…”
mentioning
confidence: 87%
“…Zinc oxide has been widely used as functional filler in UV-absorbers for application in pharmaceutical materials, cosmetics, coating materials, and pigments (Kumar and Singh, 2008;Li et al, 2009;Yu et al, 2004). In addition, the use of zinc oxide nanoparticles is considered to be a viable method for the prevention of infectious diseases through the antimicrobial effects of zinc oxide (Li et al, 2009(Li et al, , 2010Rajendra et al, 2010;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of metal nanoparticles (NPs) into polymer film matrices has been noted as the most promising method of achieving the latter goal. [1][2][3][4][5][6] The NPs offer an antimicrobial ability because of their extremely small particle sizes, which provide an extraordinarily high ratio of surface area to volume or surface area to weight as well as an innumerable number of active surfaces. Zinc oxide (ZnO) has been reported as an interesting potential substance for use in foods in antimicrobial applications.…”
Section: Introductionmentioning
confidence: 99%